Mengatasi Darurat Kekerasan di Lingkungan Pendidikan: Penyuluhan di SMPN 11 Kupang - Putri Bhwa, Daeng Agus Vieya; Ninef, Violin Irene; Tumina, Maria Syelvrida; Tamelab, Chandika Jeklin Adelia; Mardiyah, Ainun (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: Violence in educational settings is a critical issue worldwide, particularly in Indonesia. Schools, as environments for learning and socialization, should be safe spaces, yet violence remains prevalent and often unaddressed. This community service project aimed to tackle this issue by providing a targeted counseling program for junior high school students in Kupang, East Nusa Tenggara. Objective: The program aimed to raise awareness about violence, enhance students' understanding of its types and impacts, and equip them with skills to prevent and address violence. The project sought to empower students to take proactive steps in creating a safer school environment. Method: Conducted on December 10, 2024, at SMPN 11 Kupang, the program involved 80 students from grades VII to IX. Students were selected based on recommendations from counseling teachers. The program included a presentation on violence, followed by group discussions and simulations. Effectiveness was measured using pre-test and post-test questionnaires to assess changes in students’ knowledge and confidence. Results: Significant improvement was observed. Before the session, only 40% of students could define violence correctly, while 88% did afterward. Confidence in reporting violence increased from 50% to 90%. Group discussions also revealed a heightened awareness of creating a supportive school environment. Conclusion: The program successfully enhanced students’ knowledge and confidence in addressing violence, highlighting the importance of educational interventions. Future programs should incorporate parental involvement to ensure sustained impact.